How emotional intelligence affects college teachers’ wellbeing in China? The mediating role of work-family support - Yongping Li; Lebin Huang; Sobia Naseem; Qichao Shen (Frontiers in Psychology)
The pursuit of happiness is an individual’s goal in life, and an individual’s fulfillment in life, work, and psychology are essential dimensions of happiness. Emotional intelligence and work-family climate are important factors affecting individual happiness, but the mechanism of their influence on happiness is not well defined. This paper conducted an empirical study on the relationship between college teachers’ emotional intelligence, work-family support and wellbeing through questionnaires and structural equation modeling methods, and the results showed that (1) there are some differences in the demographic characteristics of college teachers’ emotional intelligence, work-family support, and wellbeing; (2) both college teachers’ emotional intelligence and work-family support can positively predict their wellbeing; (3) college teachers’ emotional intelligence positively predicted their work-family support and work-family support partially mediated the relationship between emotional intelligence and wellbeing. The study reveals the internal mechanism by which the emotional intelligence of college teachers affects their wellbeing and that improving their emotional intelligence and work-family support atmosphere can help enhance their wellbeing.